Case report: Transcatheter closure of a giant and tortuous right coronary artery to right ventricle fistula in an infant - Wu, Yen-Hsien; Liu, Yi-Ching; Chao, Min-Fang; Dai, Zen-Kong; Chen, I-Chen; Lo, Shih-Hsing; Hsu, Jong-Hau (Frontiers in Cardiovascular Medicine, 2022)
Congenital coronary artery fistulas (CAFs) is an uncommon congenital anomaly. While most patients are asymptomatic, life-threatening events including sudden death, myocardial ischemia, heart failure, infective endocarditis and rupture may occur. Surgical ligation was the standard choice of management of CAFs in the past. However, transcatheter closure of CAFs has been become an emerging alternative to surgery in patients with suitable anatomy. We reported a 7 month-old infant with a giant and tortuous right coronary artery to right ventricle fistula, which was successfully closed in the cath lab with an Amplatzer ductus occluder.